A study on human-task-related performances in converting conveyor assembly line to cellular manufacturing. (14th January 2008) - Kaku, Ikou; Murase, Yasuhiko; Yin, Yong
In this paper, we propose a study to analyse the human-task-related performances in converting a Conveyor Assembly Line (CAL) to cellular manufacturing, which include the possible added operational tasks (which is considered a negative factor for the conversion), the skill level and the cross-training of workers. Three theoretical models (CAL, cellular manufacturing and a joint type, CAL+CM) are constructed involving those constraints respectively. A human-factor-based training approach is also represented for the system performance improvement in cellular manufacturing. Assuming the product mix and the skill level of workers are probability variables, simulation experiments based on the data collected from the previous documents are then used to estimate the marginal impact each factor change had on the estimated performance improvement resulting from the conversion. [Received 18 January 2007; Revised 13 July 2007; Accepted 26 July 2007]